Establishing a high sensitivity detection method for SARS-CoV-2 IgM/IgG and developing a clinical application of this method. Issue 1 (1st January 2020) - Zhang, Chunyan; Zhou, Lei; Liu, Hao; Zhang, Sibing; Tian, Yaping; Huo, Junli; Li, Fei; Zhang, Yao; Wei, Bo; Xu, Dan; Hu, Jinwei; Wang, Jiayi; et al.
ABSTRACT: COVID-19 is caused by SARS-CoV-2 infection and was initially discovered in Wuhan. This outbreak quickly spread all over China and then to more than 20 other countries. SARS-CoV-2 fluorescent microsphere immunochromatographic test strips were prepared by the combination of time-resolved fluorescence immunoassay with a lateral flow assay. The analytical performance and clinical evaluation of this testing method was done and the clinical significance of the testing method was verified. The LLOD of SARS-CoV-2 antibody IgG and IgM was 0.121U/L and 0.366U/L. The specificity of IgM and IgG strips in healthy people and in patients with non-COVID-19 disease was 94%, 96.72% and 95.50%, 99.49%, respectively; and sensitivity of IgM and IgG strips for patients during treatment and follow-up was 63.02%, 37.61% and 87.28%, 90.17%, respectively. The SARS-CoV-2 antibody test strip can provide rapid, flexible and accurate testing, and is able to meet the clinical requirement for rapid on-site testing of virus. The ability to detect IgM and IgG provided a significant benefit for the detection and prediction of clinical course with COVID-19 patients.